What motivates a legislator to sponsor a bill that will never become law? The case of members of the Chilean Chamber of Deputies, 1990–2014. Issue 8 (16th November 2020) - Escobedo Aránguiz, Isai; Navia, Patricio
ABSTRACT: In countries where legislators can sponsor bills, but these bills have few chances of promulgation, motives other than seeing a bill become law must also account for bill sponsorship. After discussing the theoretical determinants of bill sponsorship, we propose five hypotheses that account for a legislator's bill sponsorship. We test these hypotheses for the case of Chile's presidential system, where only 8.6% of legislative bills were promulgated as laws between 1990 and 2014. We use data for 4602 bills presented by the 728 members of the Chamber of Deputies during those six legislative terms, totalling 30, 986 individual sponsorships. Deputies with discrete career ambitions sponsor fewer bills than legislators with progressive or static ambitions. Legislators with a longer tenure sponsor fewer bill. Opposition legislators do not sponsor more bills than government legislators. Legislators sponsor fewer bills in the first and last years of every term. As they have few chances of seeing their bills become laws, Chilean legislators use bills as a tool to advance their political careers and do so responding to the incentives of the electoral cycle.